Analisis dan Perancangan Electronik Customer Relationship Management Pada Klinik XYZ - Joni Suhartono (ComTech: Computer, Mathematics and Engineering Applications, 2010)
This research is to foster a good connection between company and customers. For customers, e-CRM will accommodate in interation and transaction with the company. This research is done because there are still weaknesses for customer’s service. The research method used is literature, analysis method, and also designing method in identifying system needs then design one supporting system for the company. The research result is a CRM website that gives up-to-date information and suitable for customer needs. Therefore, CRM is hoped to help company giving a better service to customers.